A Polyherbal Remedy, PurXcel improves Cadmium-induced Male Reproductive Impairment and Testicular Antioxidant Status in Wistar Rats (Nigerian Journal of Physiological Sciences, 2024)
Cadmium, despite being an environmental pollutant has a wide range of applications and causes oxidative damage to the testes and impairment of male reproductive function. PurXcel, a polyherbal remedy is said to be rich in antioxidants and improves fertility. But there are no scientific records of its effect on Cadmium-induced male reproductive impairment, hence this study. Twenty male wistar rats were randomly assigned into 4 groups of 5 rats each namely control, Cadmium-only, PurXcel-only and Cadnium+PurXcel groups. Treatment with PurXcel lasted for 28 days after which blood samples were collected and testes and epididymis harvested for evaluation of relevant parameters. Body weight changes (BWC) as well as weights of testes and epididymis were significantly reduced in Cadmium-only group (P
Keywords: PurXcel; Cadmium; reproductive parameters; oxidative stress; rat